2013
DOI: 10.3390/md11072431
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Fucoidan from Brown Seaweed Turbinaria ornata as Studied by Electrospray Ionization Mass Spectrometry (ESIMS) and Small Angle X-ray Scattering (SAXS) Techniques

Abstract: The purpose of this study is to elucidate both the chemical and conformational structure of an unfractionated fucoidan extracted from brown seaweed Turbinaria ornata collected at Nha-trang bay, Vietnam. Electrospray ionization mass spectrometry (ESI-MS) was used for determining the chemical structure and small angle X-ray scattering (SAXS) provided conformational of the structure at the molecular level. The results showed that the fucoidan has a sulfate content of 25.6% and is mainly composed of fucose and gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The product ion at m / z 97, which indicated sulfate ion [HSO 4 ] − could also be well recorded by the ESI-MS/MS spectra (Figure 4A). Previously, electrospray ionization has been shown to be an effective method for tracing the SO 4 2− ion [39,40,41,42]. It was shown that nostoxanthin with m / z 600 [M] + could lose one atom OH ( m / z 17) from the 3-position, which then it was replaced by a sulfate ion group (HSO 4 − ) resulting nostoxanthin sulfate at m / z 679.4 [M − Na] − and a fragment ion at m / z 97.3.…”
Section: Discussionmentioning
confidence: 99%
“…The product ion at m / z 97, which indicated sulfate ion [HSO 4 ] − could also be well recorded by the ESI-MS/MS spectra (Figure 4A). Previously, electrospray ionization has been shown to be an effective method for tracing the SO 4 2− ion [39,40,41,42]. It was shown that nostoxanthin with m / z 600 [M] + could lose one atom OH ( m / z 17) from the 3-position, which then it was replaced by a sulfate ion group (HSO 4 − ) resulting nostoxanthin sulfate at m / z 679.4 [M − Na] − and a fragment ion at m / z 97.3.…”
Section: Discussionmentioning
confidence: 99%
“…Fucoidan from S. mcclurei was purified further by ion-exchange chromatography [ 12 ]. Turbinaria ornata fucoidan was extracted as described by Thanh et al (2013) [ 13 ]. Fucoidans from F. evanescens , U. pinnatifida , and S. cichorioides were purified as described by Kusaykin et al (2006) [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“… Representative fucoidan structures of brown macroalgae Fucus evanescens , Fucus vesiculosus , Sargassum mcclurei , Turbinaria ornata , Saccharina cichorioides , and Undaria pinnatifida : ( A ) main chain of S. cichorioides composed of α(1→3)- l -fucosyls; ( B ) main chain of U. pinnatifida fucoidan also composed of α(1→3)- l -fucosyls; ( B’ ) branches of U. pinnatifida fucoidan [ 11 ]; ( C ) main chain of F. evanescens [ 1 ] and F. vesiculosus fucoidan [ 8 , 9 , 10 ], both composed of α(1→3)- and α(1→4)-linked l -fucosyls; ( D ) main chain of T. ornata fucoidan composed of α(1→3)- l -fucosyls [ 13 , 14 ]; ( D’ ) branches of T. ornata of α(1→3)- l -fucosyls or of β(1→4)galactosyls and mixed fucosyl-galactosyls; ( E ) main chain of S. mcclurei fucoidan made up of mainly α(1→3)- l -fucosyls [ 12 ]; and ( E’ ) branches or inserts in the main chain of S. mcclurei fucoidan. In all fucoidan structures: R 1 : −H or −SO 3 − ; R 2 : −H, −SO 3 − or H 3 COC−; R 3 : SO 3 − , H 3 COC− or branches; and R 4 : SO 3 − or branches.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29] Its chemical composition is relatively simpler because it is mainly composed of l-fucose and sulfate residues. On the basis of the results of methylation, fractionation, and on recent gas chromatography-mass spectrometry data, [27][28][29] it was suggested that the core region of Fucoidan was primarily a polymer of α-(1→3)-linked L-fucose with sulfate groups substituted at the C-4 position on some of the fucose units; fucose was also attached to this polymer to form branched points, one for every 2 to 3 fucose residues within the chain. Although the main goal of our study was to provide a stable 68 Ga-Fucoidan for imaging P-selectin expression on plaques rather than to characterize its structure, it is assumed that in the stable TcFucoidan.…”
Section: Discussionmentioning
confidence: 99%